Incidence of appendices of the testis and epididymis in children who underwent groin/scrotal surgeries in a tertiary hospital in Enugu, Nigeria - Kevin Emeka Chukwubuike (Archives of Clinical Gastroenterology - Peertechz Publications, 2021)
Background: Appendices of the testis and epididymis are small congenital structures attached to the testis and epididymis respectively. The aim of this study was to assess the incidence of appendices of the testes and epididymis in children who had inguinal and scrotal surgeries.  Materials and methods: This was a retrospective study of children aged 15 years and younger who underwent groin/scrotal surgeries between January 2015 and December 2019 at the pediatric surgery unit of Enugu State University Teaching Hospital Enugu (ESUTH), Nigeria. During the surgery, the presence or absence of appendices of testis and epididymis were assessed.  Results: A total of 521 inguinal/scrotal surgeries were performed during the study period but only 378 patients had appendices of the testis and epididymis: This gives an incidence of 72.6%. Infants were mostly affected and the right testis had more appendices. There were more inguinal hernia/hydrocele and herniotomy was the most performed surgical procedure. Surgical site infection was the most common post-operative complication but there was no mortality.  Conclusion: Appendices of the testes and epididymis although may be small and vestigial in children, it is quite common in children.